Do karyotypic abnormalities exist in young infertile women with diminished ovarian reserve? - Naredi, Nikita; Sahoo, Ipsita; Lele, Prasad R.; Agrawal, Antara; P., Sandeep Sethumadhavan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Women are endowed with a finite number of oocytes, which decrease in number and quality over time. Environmental factors, hormonal influence, iatrogenic and genetic factors impact the ovarian reserve. Diminished ovarian reserve indicating a reduction in the quantity and quality of ovarian follicular pool in women of reproductive age affects 10% women seeking fertility treatment. Objective was to find out karyotypic abnormalities in young infertile women with diminished ovarian reserve. Methods: This retrospective study was carried out over a period of one year at the Assisted Reproductive Technology Centre of a tertiary care public sector hospital. Medical records including the infertility data of 784 couples who underwent In vitro fertilization cycle during the study period was analysed. A total of 104 women with diminished ovarian reserve as evidenced by anti-Mullerian hormone (AMH) value less than 1.1 ng/ml were included in the study. Results: Out of 104 women with DOR, only 5 women (5 %) had slight variation in karyotype like 46XX 1qh+, 46XX 15ps+, 46XX 16qh+ which are normal polymorphic variations seen in general population. Remaining 99 (95%) women had normal female karyotype (46 XX). Conclusions: Women with diminished ovarian reserve mostly have a normal female karyotype.